Estimation of hygroscopic of electrotechnical materials by dynamic speckle technique - Bertolini, Guillermo Ramón (2013)
Dynamic speckle laser (DLS) technique has been applied to the analysis of different biological systems, inorganic materials and industrial processes. In this paper, we use this technique to analyze the hygroscopic properties of different types of porcelain and papers for electrotechnical purposes. Experimental speckle results showed different behavior depending on physicochemical and textural properties of the samples.